A rare case of cervical fibroid presenting as retained placenta with postpartum hemorrhage - Chowdhury, Meenakshi; Gupta, Vineeta; Jain, Vidushi Jyala; Bhardwaj, Aparna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Fibroids during pregnancy are often asymptomatic but sometimes may lead to various complications and unusual presentations. We are reporting an unusual case of cervical fibroid during pregnancy that presented as retained placenta with postpartum hemorrhage following a full term normal vaginal delivery.